Investigating preoperative myoglobin level as predictive factor for acute kidney injury following cardiac surgery with cardiopulmonary bypass: a retrospective observational study - Kuen Su Lee; Hyun Joong Kim; Yoon Sook Lee; Yoon Ji Choi; Sang Min Yoon; Woon Young Kim; Jae Hwan Kim (Brazilian Journal of Anesthesiology, 2023)
Background: Early identification of patients at risk of AKI after cardiac surgery is of critical importance for optimizing perioperative management and improving outcomes. This study aimed to identify the association between preoperative myoglobin levels and postoperative acute kidney injury (AKI) in patients undergoing valve surgery or coronary artery bypass graft surgery (CABG) with cardiopulmonary bypass. Methods: This retrospective study included 293 patients aged over 17 years who underwent valve surgery or CABG with cardiopulmonary bypass. We excluded 87 patients as they met the exclusion criteria. Therefore, 206 patients were included in the final analysis. The patients... demographics as well as intraoperative and postoperative data were collected from electronic medical records. AKI was defined according to the Acute Kidney Injury Network classification system. Results: Of the 206 patients included in this study, 77 developed AKI. The patients who developed AKI were older, had a history of hypertension, underwent valve surgery with concomitant CABG, had lower preoperative hemoglobin levels, and experienced prolonged extracorporeal circulation (ECC) times. Multivariate logistic regression analysis revealed that preoperative myoglobin levels and ECC time were correlated with the development of AKI. A higher preoperative myoglobin level was an independent risk factor for the development of cardiac surgery-associated AKI. Conclusions: Higher preoperative myoglobin levels may enable physicians to identify patients at risk of developing AKI and optimize management accordingly.